Método para avaliação digital da adequação de sistemas produtivos existentes a alterações de engenharia de produto no contexto da indústria automotiva - Iaksch, Jaqueline Sebastiany (2018)
Increasing digitalization allows the reuse of legacy work, more effectivity in decision-making processes, in addition to more reliable planning and estimates during the Product Development Process. However, current industry practices still points to the isolation of knowledge domains. Ensure that the knowledge regarding to the manufacturing process is taken in account since the begining of the Product Development Process avoids problems in later stages throughout the product life cycle because all the production constrains have been raised. With the application of the concepts of the Digital Thread approach introduces the opportunity to intelligently integrate knowledge into product development in the form of a "digital factory" capable of directing and supporting all stages of the product life cycle. Thus, the objective of this research was the elaboration of an ontological model and application method capable of evaluating, in real time, the adequacy of the existing production systems, integrating the project and process information. Design Science Research was used as methodological framework for the development of this method. In this way, six steps were performed: (i) problem identification and motivation; (ii) definition of the objectives of the solution; (iii) design and development; (iv) demonstration; (v) evaluation; and, (vi) reporting of results. The solution shows itself pertinent because through the description of the manufacturing systems, it contributes to the digital evaluation and facilitates the decision making regarding productive systems, as well as the recovery, reutilization and data management. This work was focused on the study of a specific production line of a multinational company in the automotive sector, however the model could be adapted to other segments.